High-temperature oxidation of methyl isopropyl ketone: A shock tube experiment and a kinetic model - Cheng, Jia; Zou, Chun; Lin, Qianjin; Liu, Shibo; Wang, Yunpeng; Liu, Yang (Combustion and flame, 2019)
Pentanone has three types of isomers: 3-methyl-2-butanone (methyl isopropyl ketone, MIPK), 3-pentanone (diethyl ketone, DEK) and 2-pentanone (methyl propyl ketone, MPK). Since MIPK is the smallest branched ketone and a promising biofuel, it is important to fully understand its combustion kinetics. In this work, the ignition delay times were measured in the temperature range from 1150 to 1600 K at pressures from 1 to 5 bar and for the equivalence ratios of 0.5, 1.0 and 1.5 (Mixes 1–9). A high-temperature detailed combustion kinetic model for MIPK was developed via a hierarchical method. Previous theoretical computations of the H-atom abstraction by HO˙2 and O˙H from the tertiary carbon of MIPK were adopted, and the reaction rate coefficients of H-abstraction by H˙ from the MIPK tertiary carbon were calculated via quantum chemical techniques. The rate coefficients of the reactions that are related to the acetyl group and the isopropyl group of MIPK were estimated by analogy with MPK and DIPK, respectively. Eleven elementary reactions in the submodel that are related to MIPK were selected for the optimization due to the poor prediction performance of the raw model. The self-adaptive differential evolution algorithm was applied to optimize the raw kinetic model based on the ignition delay times of Mixes 1–6. The optimized MIPK model was validated against the ignition delay times of Mixes 7–9. A brute-force sensitivity analysis, in combination with a flux analysis, demonstrates that the amount of unsaturated fuel-related stable intermediate products is the key factor that determines the reactivity of MIPK and DEK.